Case Report: Interferon-Alpha-Induced Neuromyelitis Optica Spectrum Disorder - Rao, Jie; Xu, Na; Sun, Jing; Li, Yan; Fu, Fangwang (Frontiers in Neurology, 2022)
Background and Objectives To describe a new case of neuromyelitis optica spectrum disorder (NMOSD) induced by the administration of interferon-alpha (IFNα) and raise awareness of this rare drug-induced disease of IFNα treatment. Methods A single case study and comprehensive literature review of eight cases. Results A 24-year-old man was diagnosed with cerebral venous thrombosis and essential thrombocythemia. He had been undergoing IFNα treatment (IFNα-2b, 3 million IU per day) without any side effects for 18 months, at which point the patient developed persistent hiccups, nausea, urinary retention, and numbness. Spinal magnetic resonance imaging revealed a longitudinal abnormality extending from the medulla to the entire spinal cord. The patient was positive for anti-aquaporin-4 antibody (AQP4-IgG) in both the serum and cerebrospinal fluid, which confirmed the diagnosis of NMOSD. Thus, recombinant IFNα-2β was suspended immediately. Because his condition did not improve after 6-day treatment of methylprednisolone pulse therapy (1000 mg for 3 days, then 500 mg for 3 days), intravenous immunoglobulin (0.4 g/kg/day for 5 days) were administered. The patient gradually improved. Low-dose prednisolone and mycophenolate mofetil were subsequently administered as a long-term treatment. The patient was discharged with subtle limb numbness and their EDSS score was 1. At the 1-year follow-up, the patient had not relapsed and tested negative for AQP4-IgG. We identified a further eight patients with IFNα-induced NMOSD. The median onset age was 59 years, and the median time of IFNα exposure was 18 months. Optic neuritis was the most common initial symptom (five, 55.6%), followed by myelitis in three patients and area postrema syndrome in one patient. More than half (five, 55.6%) of the patients were monophasic. After IFNα discontinuation and immunotherapy, most (seven, 77.8%) patients remained relapse-free. However, only one patient was free of sequelae. Conclusion This study highlights the potential pathogenic risk of NMOSD of IFNα treatment. Given the high disability rates of this rare drug-induced disease, it is crucial to monitor the early manifestations of NMOSD during IFNα treatment.